Microfabrication of Plasmonic Biosensors in CYTOP Integrating a Thin SiO2 Diffusion and Etch-barrier Layer - Hanif, Raza (2011)
A novel process for the fabrication of Long Range Surface Plasmon Polariton (LRSPP) waveguide based biosensors is presented herein. The structure of the biosensor is comprised of Au stripe waveguide devices embedded in thick CYTOP claddings with a SiO2 solvent diffusion barrier and etch-stop layer. The SiO2 layer is introduced to improve the end quality of Au waveguide structures, which previously deformed during the deposit of the upper cladding process and to limit the over-etching of CYTOP to create micro-fluidic channels. The E-beam evaporation method is adapted to deposit a thin SiO2 on the bottom cladding of CYTOP. A new micro-fluidic design pattern is introduced. Micro-fluidic channels were created on selective Au waveguides through O2 plasma etching. The presented data and figures are refractive index measurements of different materials, thickness measurements, microscope images, and AFM images. Optical power cutback measurements were performed on fully CYTOP-cladded symmetric LRSPP waveguides. The end-fire coupling method was used to excite LRSPP modes with cleaved polarization maintaining (PM) fibre. The measured mode power attenuation (MPA) was 6.7 dB/mm after using index-matched liquid at input and output fibre-waveguide interfaces. The results were compared with the theoretical calculations and simulations. Poor coupling efficiency and scattering due to the SiO2 are suspected for off-target measurements.